2017
DOI: 10.3341/kjo.2016.0095
|View full text |Cite
|
Sign up to set email alerts
|

Visual Fatigue Induced by Viewing a Tablet Computer with a High-resolution Display

Abstract: PurposeIn the present study, the visual discomfort induced by smart mobile devices was assessed in normal and healthy adults.MethodsFifty-nine volunteers (age, 38.16 ± 10.23 years; male : female = 19 : 40) were exposed to tablet computer screen stimuli (iPad Air, Apple Inc.) for 1 hour. Participants watched a movie or played a computer game on the tablet computer. Visual fatigue and discomfort were assessed using an asthenopia questionnaire, tear film break-up time, and total ocular wavefront aberration before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 28 publications
(30 reference statements)
5
89
0
14
Order By: Relevance
“…; Kim et al. ). The questions were modified to reflect the characteristics of Chinese college students.…”
Section: Methodsmentioning
confidence: 98%
“…; Kim et al. ). The questions were modified to reflect the characteristics of Chinese college students.…”
Section: Methodsmentioning
confidence: 98%
“…The long‐term ocular effects of smartphone and handheld digital device use are unknown. However, a range of short‐term ocular surface discomfort, visual discomfort and aesthenopic symptoms are reported with smartphones and tablets use . Ocular surface discomfort includes sore eyes, dryness, stinging, burning, itchiness and irritation.…”
Section: Summary Of Significant Effects Of Smartphone Use On Symptomsmentioning
confidence: 99%
“…Several studies have shown one hour of tablet or smartphone use increases eye strain and blur in young adults by as much as five times . It is unclear whether these collective symptoms are due to effects on the accommodative/vergence system, the ocular surface (including blinking) or a combination of both.…”
Section: Summary Of Significant Effects Of Smartphone Use On Symptomsmentioning
confidence: 99%
“…The correlation between asthenopia and digital devices abuse has been widely reported and classified in heterogeneous population into internal ocular symptoms (strain and ache), external ocular symptoms (dryness, irritation, burning), visual symptoms (blur, double vision) and musculoskeletal symptoms (neck and shoulder pain) [1][2].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone, in particular, has become the most used device that involving everyone attention during travelling, work or school activities, at home, to dinner table, restroom and even to bed before sleeping [1][2].…”
Section: Introductionmentioning
confidence: 99%